KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMP SETELAH PENERAPAN VIDEO EDUKASI DALAM PROSES PEMBELAJARAN - Nazar, Aldi M.; Sulisawati, Dwi Noviani; Hidayatin, Nur (Universitas Insan Budi Utomo, 2025)
This study aims to describe the mathematical critical thinking skills of junior high school students after the implementation of educational videos in the learning process. Critical thinking skills involve a deep thinking process, where individuals not only accept information as it is but also question, evaluate, and assess the validity of the information. This ability allows someone to analyze information objectively, evaluate various arguments, and make decisions based on logical reasoning. This study uses a qualitative research type. The researcher will take 2 data sources based on the results of the pre-test of student abilities, namely 2 students with high thinking ability criteria and low thinking ability criteria. The results of the study showed that in critical thinking, high ability students met three main indicators, namely basic support (building basic skills), elementary clarification (giving simple explanations), and inference (concluding). While low ability students showed weaknesses in giving simple explanations (elementary clarification), they had good abilities in building basic skills (basic support) and concluding (inference). This shows that although R1 and R2 are able to use data and evidence effectively and draw logical conclusions, they have difficulty explaining concepts or information simply and clearly.